Análisis de la microfranquicia como modelo empresarial innovador e incluyente aplicado en el sector gastronómico: Caso: Mipyme colombiana - Verónica Tordecilla-Acevedo; James Manuel Pérez Morón; Andrea Carolina Moscote Palomino (Atlantic Review of Economics (ARoEc), 2018)
– With this document, we want to know the business model of the Microfranchises and how they contribute to the generation of jobs and sustainable income in the low-income population of the Colombian Caribbean region. For this, the state of the art is presented with the concepts of franchise models, microfranchises and their evolution over the years. The results of the review show that even though there is no specific legal regulation, this has not been a problem for the creation of Microfranchises in Colombia. It is also evident that increasing access to financial services for the lower income population is necessary, but not the only ingredient as a solution to poverty, increasing access to scalable business opportunities as an important aspect; Microfranchises as a proven business format provide such access with key characteristics such as self-sustainability, the amount of investment required and the social impact it can generate; in this regard, it is important to continue the work of sensitization of the business model among entrepreneurs, national and international partners and experts in the thematic consultants. Finally, it points out that the methodology used in the study is theoretical, which required review of literature, from which was extracted the conclusions of the authors, not without first considered the context of the Colombian Caribbean coast.
Keywords: R11; M13; I30; 330; Microfranchises; microcredit; franchising; sustainable development; end of poverty